Policy actions for scaling Africa’s climate adaptation: Bridging technical, institutional, and implementation gaps - Odhiambo Isaack; Njuguna, Lucy; Mundia, Carolyne; Kimanzi, Meshack; Atieno, Tessie; Kung'u, Fredrick; Denje, Telvin; Awolala, David; Chilambe, Pedro Anglaze; Wamukoya, George (2025)
Africa’s growing exposure to climate hazards necessitates a decisive transition from broad, fragmented adaptation pledges to actionable, integrated national climate strategies. Persistent implementation gaps—marked by institutional fragmentation, budgetary constraints, and underdeveloped monitoring, reporting, and verification (MRV) and data systems—demand enhanced inter-ministerial coordination, streamlined African-specific technical guidelines, and targeted capacity building at national and sub-national levels. To advance this agenda, scaling up proven approaches is critical. These include leveraging analytical and digital planning tools (such as FABLE and LEAP), fostering cross-ministerial collaboration, and embedding locally led adaptation practices. Such measures can catalyze more ambitious, inclusive, and sector-responsive adaptation action, particularly within the continent’s vital agriculture and food systems.